Measures to Control Invasive Crayfish Species in Switzerland: A Success Story? - Krieg, Raphael; King, Alex; Zenker, Armin (Frontiers in Environmental Science, 2020)
Invasive crayfish species were first documented in Switzerland in the 1970s. Today, North American crayfish species dominate in most major lakes and streams in Switzerland. In combination with the crayfish plague, they pose a substantial threat to our native crayfish. Over the past 20 years, various techniques have been applied to reduce negative impacts of these invasive crayfish in Switzerland: eradication (temporary drainage or destruction of a water system, biocides), suppression (intensive trapping, electricity introduction of predatory fish) and containment (construction of crayfish barriers). Temporary drainage or filling-in of isolated ponds, in combination with calcium hydroxide application has been successful in eradicating populations of invasive crayfish. However, trapping and introduction of predatory fish led to a reduction in population density but neither method has ever caused the extinction of a population. Invasive crayfish have not yet reached crayfish barriers, therefore, long-term functionality of these barriers still needs to be proven. Nevertheless, functional controls with native crayfish have shown that barriers prevent their upstream movement. Implementation of crayfish barriers is the most promising method to protect native crayfish from displacement by invasive crayfish species. Many measures are expensive, time consuming, and show little or no success in controlling invasive crayfish. Therefore, we recommend to focus on implementing drastic measures, such as filling-in or draining of isolated waters or a combination of various methods to maximise the reduction of population size.